Implementasi Integrasi Perkebunan Kelapa Sawit, Peternakan Sapi dan Perikanan Tambak di Gampoeng Teupin Panah Kecamatan Kaway XVI Aceh Barat - Syahril, Syahril; badli, saiful (Universitas Teuku Umar, 2023)
The instability of the price of oil palm Fresh Fruit Bunches (FFB) and the operational costs of oil palm plantations are problems that continue to occur and are very difficult to control. This condition creates uncertainty for oil palm farmers in obtaining income and spending costs needed to operate oil palm plantations.Method of implementing this activity begins with identifying problems that occur among oil palm farmers, either directly in several locations in West Aceh or indirectly through the latest literature from various sources. Then the next stage is conducting an FGD with the Regional Government of West Aceh Regency and entrepreneurs of palm oil, cattle farms and fish farms which will produce recommendations and strategies for implementing the integration of the three businesses in question. Next, they will build cowsheds and fish ponds using a self-management system for Gampoeng Teupin Panah farmers. The final stage is to make an offer to the community and other parties to invest in cattle using the mawah system and also raising pond fish using a profit sharing system. Then the final stage is to socialize the concept of integration to the community so that it can be applied to their own land.The results achieved in this service are as follows: (1). Creating a cow pen and procuring cattle using the mawah system (2) Creating a pond for tilapia and catfish and directly releasing fish seeds into the pond; (3) Conduct program outreach to oil palm farmers in Gampoeng Teupin Panah, Kaway XVI District, West Aceh. Through this integration program, farmers are increasingly motivated and focused on developing oil palm plantations, cattle farms and pond fisheries in an effort to increase their income stably. Then the success of this program can meet the demand for beef and pond fish, especially in West Aceh Regency and surrounding areas.